The law alteration on artificial intelligence in reducing Islamic bank’s profit and loss sharing risk - Yuspin, Wardah; Wardiono, Kelik; Budiono, Arief; Gulyamov, Said (Legality : Jurnal Ilmiah Hukum, 2022)
Artificial Intelligence is categorized into the domain of computer science focused on creating intelligent machines that function like humans. Artificial Intelligence supports institutions including Islamic Financial Services in learning, making decisions, and providing useful predictive analytics. The progress and promise that artificial intelligence has made and presented in finance have so far been remarkable, allowing for cheaper, faster, closer, more accessible, more lucrative, and more efficient finance especially during the pandemic Covid-19 when people are required to stay at home yet still doing a banking transaction. Despite the incredible progress and promise made possible by advances in financial artificial intelligence, it nevertheless presents some serious perils and limitations. Three categories of risks and limitations involve the rise of virtual threats and cyber conflicts in the financial system, society's behavioral changes, and legal amendments that cannot respond to technological developments, especially in developing countries. The main objective of this article is to evaluate the operations of the potential risks that may arise in the use of Artificial Intelligence in Islamic finance services, especially dealing with the legal arrangement that is supposed to be in line with business development. Indonesia is a country that adheres to civil law system, in which every legal arrangement is supposed to be based on written law. The lack of this legal system is where the speed of legal changes cannot keep up with the pace of technological development, which is present as a hinder to the development of Artificial Intelligence in the financial system. This article concludes that Artificial Intelligence will have a huge impact in the future on the Islamic Finance industry, but in the Indonesian context, it still needs various efforts to reduce the potential risk that eventually has a big impact on the progress of Islamic banks.